THE USE OF BLOG TO INCREASE STUDENTS’ WRITING SKILL - Muhammad Syahrul; Hasnawati Latief; Ardiana (Journal of Language Testing and Assessment, 2021)
This research finding out whether the blog increases the students’ writing skill. In this study, researcher used in this quantitative research is a pre-experimental method. This kind of study allows the researcher to look at the effects of at least one independent variable and one dependent variable. In this research, the researcher wanted to see whether the treatment make a difference or no. Population The population of the research was the eleventh grade students of SMA Negeri 4 Jeneponto in the academic year of 2019/2020. Sample, the sample was selected by using cluster random sampling technique. The researcher chose one class as the sample. Research Instrument, the instrument used in this research was writing test. To test writing ability the researcher will ask the students to write three paragraphs. There will be two tests, namely pre-test & post-test.